Cultural heritage information access and management - Ruthven, Ian 1968-; Chowdhury, G. G. (Gobinda G.) (iResearch series., 2015)
Currently, the Internet and digitization have offered new opportunities for providing better and wider access, but they also pose new challenges. This collection of essays addresses accessing and managing cultural heritage information resources.